Simulating cardiac signals on 3D human models for photoplethysmography development - Wang, Danyi; Chahl, Javaan (Frontiers in Robotics and AI, 2024)
Image-based heart rate estimation technology offers a contactless approach to healthcare monitoring that could improve the lives of millions of people. In order to comprehensively test or optimize image-based heart rate extraction methods, the dataset should contain a large number of factors such as body motion, lighting conditions, and physiological states. However, collecting high-quality datasets with complete parameters is a huge challenge. In this paper, we introduce a bionic human model based on a three-dimensional (3D) representation of the human body.By integrating synthetic cardiac signal and body involuntary motion into the 3D model, five well-known traditional and four deep learning iPPG (imaging photoplethysmography) extraction methods have been used to test the rendered videos. To compare with different situations in the real world, four common scenarios (stillness, expression/talking, light source changes and physical activity) have been created on each 3D human. The 3D human can be built with any appearance and different skin tones. A high degree of agreement was achieved between the signals extracted from videos with the synthetic human and videos with a real human -the performance advantages and disadvantages of the selected iPPG methods are consistent for both real and 3D humans. This technology has the capability to generate synthetic humans within various scenarios, utilizing precisely controlled parameters and disturbances. Furthermore, it holds considerable potential for testing and optimizing image-based vital signs methods in challenging situations where real people with reliable ground truth measurements are difficult to obtain, such as in drone rescue.